Pergeseran Distribusi Kekuasaan Antara Pemerintah Pusat Dengan Pemerintah Daerah - Jurnal Governance Jurnal Kebijakan & Manajemen Publik; Farina Gandriyani (Governance, JKMP (Governance, Jurnal Kebijakan & Manajemen Publik), 2011)
The existence of Local Government is so urgent, specially for country that practices unity system. In the same manner as Indonesia that has very large region, with the inhabitants concentrated into certain area whose societies are very heterogeneous observed both from ethnic, religion, culture aspects and the economic lifecycle background, etc. Beside this such heteroginity, each region has various natural resources. The matter is how to give service for the society in the region.In such mindset, the region autonomy is an political instrument and also an administration/management instrument used to optimize local resources, so it could be used to make benefit largely for the furtherance of society in region, particularly to face the global challenge in order to push the society employing, to make initiative and creativity grow, to raise society involvement and evolve democracy climate in region.